Comparison of nalbuphine and propofol verses pentazocine and promethazine in tympanoplasty surgeries under monitored anesthesia care - Deepali Valecha,; Monika Gandhi,; Ravi Barde,; Agrawal, Arpit; Kishore Kumar Arora, (Asian Journal of Medical Sciences, 2022)
Background: A middle ear surgery (tympanoplasty), is done under various modes of anaesthesia such as local anaesthesia (LA), general anaesthesia (GA) or sedation with local anaesthesia (MAC). It is usually performed under MAC providing advantages of rapid onset, allowing hearing test intraoperatively and early mobilization of the patient. Aims and Objectives: The aim of this study was to compare effectiveness of nalbuphine and propofol with pentazocine and promethazine combination for intraoperative sedation under monitored anesthesia care for tympanoplasty under local anesthesia (LA). Materials and Methods: A total 60 patients undergoing tympanoplasty under LA divided in to two groups randomly to receive either IV nalbuphine (50 mcg/kg) and propofol 750 mcgs/kg in 10 min followed by a maintenance infusion at the rate of 25 mcg/kg/min. Group N or pentazocine 0.6 mg/Kg and Inj. Promethazine 0.5 mg/kg IV diluted in 10 ml normal saline over 10 min followed by 25 mcg/kg/min infusion of normal saline (Group P). Sedation was titrated to Ramsay Sedation Score (RSS) of 3. Vital parameters such as HR, BP, SpO2, RSS, visual analog scale score (VAS), requirement of rescue analgesics, mean bleeding score, and surgeon satisfaction score (Likert Scale) were recorded and analyzed. Results: RSS was higher and VAS score was lower in Group N at 30, 60, 90, and 120 min (P<0.05) that mean bleeding score was lower in Group N as compare to Group P which was statistically significant. Conclusion: Nalbuphine and propofol combination are superior to pentazocine and promethazine combination in terms of producing better analgesia, sedation with batter surgical field.